ANALISIS PEMBELAJARAN MENDALAM BERBASIS ASESMEN DI SEKOLAH DASAR - Rahmadini, Arsita Listya; Sutrisno, Tri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the implementation of assessment-based deep learning in a primary school classroom, focusing on how the principles of meaningful, mindful, and joyful learning are enacted through formative and authentic assessment practices. A qualitative descriptive approach was employed, involving 15 fifth-grade students and their homeroom teacher at SDN Geneng 02. Data were collected through classroom observation across several learning sessions, semi-structured interviews with the teacher, and documentation of lesson plans and student work, then analyzed using the interactive model of Miles and Huberman comprising data reduction, data display, and conclusion drawing. The findings indicate that the teacher gradually integrated the three principles of deep learning into daily instruction: meaningful learning was realized through contextual tasks connected to students' everyday experiences; mindful learning appeared in reflective activities and student self-monitoring; and joyful learning was expressed through collaborative games and a warm classroom climate. Formative assessment, carried out through questioning, portfolios, and peer feedback, functioned as the main instrument connecting these three principles, allowing the teacher to continuously monitor students' conceptual understanding rather than relying solely on end-of-unit tests. Most students showed a high level of engagement and enthusiasm, although reflective and metacognitive skills still required further scaffolding. These findings suggest that assessment-based deep learning is feasible in resource-limited primary schools when teachers deliberately design assessment as an integral part of the learning process rather than as a separate evaluative activity.